Pricing sin stocks: Ethical preference vs. risk aversion - Stefano Colonnello; Giuliano Curatola; Alessandro Gioffré (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2017)
We develop a model that reproduces the return and volatility spread between sin and non-sin stocks, where investors trade off dividends with the ethical assessment of companies. We relax the assumption of boycott behaviour and investigate the role played by the dividend share of sin stocks on their return and volatility spread relative to non-sin stocks. We empirically show that the dividend share predicts a positive return and volatility spread. This pattern is reproduced by our model when dividends and ethicalness are complementary goods and investors are sufficiently risk averse.
urn:nbn:de:gbv:3:2-77283
Keywords: D51; D91; E20; G12; 330; asset pricing; general equilibrium; sin stocks